Impact of Customer Relationship Management (CRM) on Customer Satisfaction and Loyalty: A Systematic Review - Bin-Nashwan, Saeed Awadh; Hassan, Haslinda (Journal of Advanced Research in Business and Management Studies, 2020)
In this study, we review literature on Customer Relationship Management (CRM), focusing specifically on the impact of the CRM on customer satisfaction and customer loyalty. CRM is a set of practices that organizations adopt to maintain and increase their customer base. A systematic review of empirical researches from different sources of journals and conferences papers, covering the period 2005 to 2015, is carried out. The results found are diverse in terms of the publication trend, CRM classification, industries, and countries studied. The three dimensions that have been frequently used in prior studies that address the impact of CRM on customer satisfaction and customer loyalty are service quality (SQ), service access (SA), and handling complaints (HC). These factors are found to have effects on customer satisfaction and customer loyalty. The study benefits both academics and practitioners in the context of adding to the existing literature on CRM and providing insights on what drives CRM in real practice.